HUBUNGAN KARAKTERISTIK PENGETAHUAN SIKAP PADA PEMBELI DAN PEDAGANG DENGAN PENGGUNAAN KANTONG PLASTIK DI PASAR TRADISIONAL FIRDAUS KECAMATAN MEDAN TEMBUNG TAHUN 2014 - Mira Guslaida Lubis; evi naria; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT Plastic bags are often used to bring some daily necessities. The plastic bags usage will continually impact on environmental pollution because the plastic bag takes 500-1000 years to be completely degraded by soil microorganisms. The purpose of this study was to determine the characteristics knowledge correlation and attitudes of consumers and merchants with the usage of plastic bags in firdaus traditional market subdistric medan tembung in 2014. Type of research is analityc survey with a cross sectional study design. Population in this study are all consumers who shop and merchants who sell in firdaus traditional market subdistric medan tembung. Total sample is 60 peoples. Technical sampling is using purposive sampling and though of data obtained process using the chi square test and Fisher's exact. The results obtained by the existence of the correlation between occupation (p= 0,001) knowledge (p= 0,034) and attitudes (p= 0,037) with usage of plastic bags in firdaus tradisional market subdistric medan tembung. Based on research, suggested that the application of the costs to the plastic bags provided by the company or company who produce plastic bags to consumer who usage plastic bags. their campaign activities, counseling and other information media to increase knowledge, attitudes and public awareness to reduce or limit the usage of plastic bags and start to not use plastic bags in order to usage plastic bags can be reduced and the environmental pollution caused by plastic bags can be minimized and for respondents who have starts reduce, reuse, and limit the usage of plastic bags to retain concern for the environment. Keywords: Characteristics, Knowledge, Attitudes, The usage of plastic bags.